Inhibition of Bacterial Conjugation by Ribonucleic Acid and Deoxyribonucleic Acid Male-Specific Bacteriophages - Novotny, Charles (1968)
Both deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) male-specific phages, with an F-specific host range, inhibited the bacterial mating process of Escherichia coli. DNA phages prevented the formation of mating pairs but had no effect on mating pairs once they were formed. A step in RNA phage infection, prior to RNA penetration, prevented the formation of mating pairs and, in addition, prevented a fraction of existing mating pairs from completing the mating process. These findings are compatible with the hypothesis that donor cells have a single surface structure involved in both conjugation and male-phage adsorption and that this element is the F pilus.